e-Government in the Stavropol Region: Assessment of the Level of Citizens' Satisfaction with the Provision of Public and Municipal Services - NOVIKOVA, Irina Vladimirovna; P'YANOV, Aleksandr Ivanovich; RUDICH, Slavko Brankovich; IVASHOVA, Valentina Anatolievna (Journal of Advanced Research in Law and Economics, 2017)
The article analyzes the measures to introduce the model of the organization of ʽe-governmentʽ in the Stavropol Territory and presents the results of a specific sociological study to determine the level of satisfaction of citizens with its functioning. The sociological research was carried out on the basis of probabilistic (random) sampling in 5 urban and 6 rural municipalities of the Stavropol region. As a method of collecting primary data, a survey was used in the form of questionnaires and interviewing. In addition to the study of the degree of satisfaction of residents of cities and rural areas of the Stavropol Territory the quality of the work of multifunctional centers, we set out to identify the main problems in the provision of public and municipal services by these centers. An analysis of the results of the research showed that the current model of the organization of ʽe-governmentʽ in the constituent entities of the Russian Federation is ineffective and requires an institutional reorganization of the mechanisms of inter-agency cooperation.